Consumer–plant interaction strength: importance of body size, density and metabolic biomass. Issue 10 (6th February 2015) - Atkins, Rebecca L.; Griffin, John N.; Angelini, Christine; O'Connor, Mary I.; Silliman, Brian R.
<x xml:space="preserve">Abstract</x> Explaining variability in the strength and sign of trophic interactions between primary consumers and plants is a long‐standing research challenge. Consumer density and body size vary widely in space and time and are predicted to have interactive effects on consumer–plant interactions. In a southern US salt marsh, we used replicate field enclosures to orthogonally manipulate the body size (mass) and density of a dominant consumer (a snail). We investigated impacts (leaf damage and biomass) on monocultures of cordgrass, the foundation species, over three months. Increasing consumer density and body size increased leaf damage additively and, as predicted, multiplicatively reduced plant biomass. Notably, size and density determined the sign of consumer impact on plants: low to medium densities of small consumers enhanced, while high densities of large consumers strongly suppressed, plant biomass. Finally, total consumer metabolic biomass (mass0.75) within an enclosure parsimoniously explained plant biomass response, supporting theoretical predictions and suggesting that multiplicative effects of density and body size resulted from their effects on total metabolic biomass. The consequences of changes in consumer density and body size resulting from anthropogenic perturbations may therefore be predicted based on metabolic biomass. <boxed-text content-type="box" position="anchor" orientation="portrait"> Synthesis Consumer size, density and biomass can all strongly affect consumer–plant interactions. Though density and body size have been extensively studied as drivers of variation in interaction strength, the role of biomass as the ultimate driver has been less appreciated. We manipulated body size and density of a single consumer species and, based on metabolic theory, integrated these into a single variable: total metabolic biomass. Our results suggest that changes in interaction strength attributed to size or density may in fact be due to changes in metabolic biomass. This metric could thus serve as a useful tool in further understanding species interactions. </boxed-text>